Proceedings of the 4th Annual Symposium on Cloud Computing 2013
DOI: 10.1145/2523616.2523622
|View full text |Cite
|
Sign up to set email alerts
|

On fault resilience of OpenStack

Abstract: Cloud-management stacks have become an increasingly important element in cloud computing, serving as the resource manager of cloud platforms. While the functionality of this emerging layer has been constantly expanding, its fault resilience remains under-studied. This paper presents a systematic study of the fault resilience of OpenStack-a popular open source cloud-management stack. We have built a prototype fault-injection framework targeting service communications during the processing of external requests, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…Table 4 shows these injection points and their major responsibilities for tasks in the scope of our experiments. These injection points are potentially error-prone because of network and I/O, and they reflect general and typical failure patterns that have been well studied [17,19,20]. During the experiment, we enable these injection points one at a time and set every enabled injection point with a 25% chance to trigger an execution problem.…”
Section: Experiments Designmentioning
confidence: 99%
“…Table 4 shows these injection points and their major responsibilities for tasks in the scope of our experiments. These injection points are potentially error-prone because of network and I/O, and they reflect general and typical failure patterns that have been well studied [17,19,20]. During the experiment, we enable these injection points one at a time and set every enabled injection point with a 25% chance to trigger an execution problem.…”
Section: Experiments Designmentioning
confidence: 99%
“…More recently, fault injection techniques and tools have been developed for cloud computing software. In [27], Ju et al discuss the testing of fault resilience of the OpenStack cloud computing platform. They inject faults targeting communication among OpenStack services, namely service crashes (by killing service processes) and network partitions (by disabling communication between two subnets).…”
Section: Related Workmentioning
confidence: 99%
“…A systematic study on fault resilience of OpenStack [15] is reported in [18]. Openstack is one of the most important open cloud computing software, that controls compute, storage and networking resources in a whole data center, managed and provisioned through a web-based dashboard, commandline tools or a RESTful API.…”
Section: B Fault Injection Testing Of Cloud Management Stackmentioning
confidence: 99%